Meningkatkan Aktivitas Belajar Dan Keterampilan Berpikir Kritis Menggunakan Kombinasi Model Problem Based Learning Dan Pendekatan Tpack Pada Muatan IPA Siswa Sekolah Dasar - Dewi Normaya; Maimunah (CV. ITTC INDONESIA, 2023)
The problem in this research is the lack of science process skills, students do not work together, students' critical thinking skills are less developed, students do not understand the material, and learning has not integrated technology. The purpose of this study was to determine teacher activity, student activity, critical thinking skills and learning outcomes of fifth grade students at Kelayan Timur 8 Elementary School by applying the